White matter abnormalities in treatment-naive adolescents at the earliest stages of Anorexia Nervosa: A diffusion tensor imaging study. (30th August 2017) - Gaudio, Santino; Quattrocchi, Carlo Cosimo; Piervincenzi, Claudia; Zobel, Bruno Beomonte; Montecchi, Francesca Romana; Dakanalis, Antonios; Riva, Giuseppe; Carducci, Filippo
Abstract: Few studies have examined white matter (WM) integrity in long-lasting Anorexia Nervosa (AN) patients using Diffusion Tensor Imaging (DTI). In this paper, we investigated WM integrity at the earliest stages of AN (i.e. less than 6 months duration). Fourteen treatment-naive female adolescents with AN restrictive type (AN-r) in its earliest stages and 15 age-matched healthy females received brain MRI. Fractional Anisotropy (FA), Axial Diffusivity (AD), Radial diffusivity (RD), and Mean Diffusivity (MD) maps were computed from DTI data using Tract-Based Spatial Statistics analysis. AN-r patients showed FA decreases compared to controls (pFWE < 0.05) mainly in left anterior and superior corona radiata and left superior longitudinal fasciculus. AN-r patients also showed decreased AD in superior longitudinal fasciculus bilaterally and left superior and anterior corona radiata, (pFWE < 0.05). No significant differences were found in RD and MD values between the two groups. FA and AD integrity appears to be specifically affected at the earliest stages of AN. Alterations in the microstructural properties of the above mentioned tracts, also involved in cognitive control and visual perception and processing, may be early mechanisms of vulnerability/resilience of WM in AN and sustain the key symptoms of AN, such as impaired cognitive flexibility and body image distortion. Highlights: Specific white matter (WM) tracts appear altered at the earliest stages of anorexia (AN). Altered WM tracts are involved in cognitive control and visual perception/processing. These alterations could be early mechanisms of vulnerability/resilience of WM in AN. These WM alterations could sustain cognitive inflexibility and body image distortion of AN.